Pengaruh Penerapan E-Billing Dan E-Filing Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi Pada Kantor Pelayanan Pajak Pratama Jakarta Jatinegara Tahun 2022 - Nisa, Khairun; Prasetiyani, Erni (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This study was conducted to determine the effect of implementing ebilling and e-filing taxation on individual taxpayer compliance at KPP Pratama Jakarta Jatinegara in 2022. This type of research is quantitative research using simple random sampling method. The population of this study is an individual taxpayer who is registered on KPP Pratama Jakarta Jatinegara. The sample used was 100 respondents determined by slovin formula. The data of this study were obtained using questionnaires that have been distributed to taxpayers. Data analysis in this study using multiple linear regression analysis and hypothesis testing with the help of SPSS program version 24. The results of this study showed that the application of e-billing effect on individual taxpayer compliance, the application of e-filing effect on the compliance of individual taxpayers, as well as the implementation of e-billing and e-filing there is a simultaneous significant effect of 59.1% on the compliance of individual taxpayers on KPP Pratama Jakarta Jatinegara, and the remaining 40.9% were influenced by other variables not discussed in this study.